High resolution anoscopy may be useful in achieving reductions in anal cancer local disease failure rates. (25th December 2013) - Goon, P.; Morrison, V.; Fearnhead, N.; Davies, J.; Wilson, C.; Jephcott, C.; Sterling, J.; Crawford, R.
<x xml:space="preserve">Abstract</x> Anal cancer is uncommon, with an incidence rate of 0.5–1.0 per 100 000 of the population but incidence rates have been steadily increasing over the last 3 decades. Biological and epidemiological evidence have been mounting and demonstrate that anal cancer has many similarities to cervical cancer, especially in regard to its aetiology. High‐resolution anoscopy (HRA) of the anal region – analogous to colposcopy of the cervix, is a technique that is not well‐known in the medical and surgical fraternity. Evidence to support the use of HRA for detection and treatment in the surveillance of AIN exists and strongly suggests that it is beneficial, resulting in reduced rates of cancer progression. Pilot data from our study showed a local disease failure rate of 1.73 per 1000 patient‐months compared with a published rate of 9.89 per 1000 patient‐months. This demonstrates a 5.72‐fold reduction in local disease failure rates of patients with T1‐T3 tumours; the data therefore suggests that use of HRA for detection and treatment in surveillance of anal cancer patients will help prevent local regional relapse at the anal site. There is an urgent need for a large, randomised controlled clinical trial to definitively test this hypothesis.